Splenic plasma cells can serve as a source of amyloidogenic light chains - Solomon, Alan (American Society of Hematology, 2009)
Bone marrow-derived clonal plasma cells, as found in systemic amyloidogenic light chain–associated (AL) amyloidosis, are presumed to be the source of light chains that deposit as fibrils in tissues throughout the body. Paradoxically, people with this disorder, in contrast to multiple myeloma, often have a low percentage of such cells, and it is unknown whether this relatively sparse number can synthesize enough amyloidogenic precursor to form the extensive pathology that occurs. To investigate whether another hematopoietic organ, the spleen, also contains monoclonal light chain–producing plasma cells, we have immunostained such tissue from 26 AL patients with the use of antiplasma cell, antifree κ and λ, and anti-V(L) subgroup-specific monoclonal antibodies (mAbs). In 12 cases, there was statistically significant evidence of a monoclonal population bearing the same κ or λ isotype as that within the bone marrow and identical to the amyloid. Our studies have shown that the spleen may be another source of amyloidogenic light chains.